Towards An Integrative View Of Corneal Proteomics In Epithelial Wound Healing - Meraj Zehra; Shamim Mushtaq; Erum Zafar; Nikhat Ahmed (ziauddin University, 2024)
Corneal epithelial wound healing is a continuous and multistep process involves cell migration proliferation and differentiation after an injury. Any defect in these processes will result in loss of corneal transparency and function. Around 135 million people are visually impaired, which illustrate the need for better understanding of corneal healing mechanisms and development of efficient ways to accelerate and improve wound healing. Delayed corneal wound healing contains the risk of bacterial infection causes corneal opacity and neovascularization that could lead to corneal blindness. It is therefore important that epithelium should rapidly regenerate after an injury. Reepithelialization involves cell migration proliferation and differentiation to restore the cornea to its highly organized architecture. The molecular mechanisms underlying these processes are yet to be established. Hence the identification of various proteins that could associate with healing process is of great significance. Key Words: Corneal Epithelium, Proliferation, Wound Healing, Migration